The Word of Mouth Effect - Fredberg, André; Wiklund, Joakim (2011)
People tend to talk more and more about experience they have with an encounter with an organization or company. Depending on the encounter was satisfying people will talk to their family and friends about the experience and either put the organization or company in a good or a bad light. When people talks amongst each other about their feelings with an encounter it is called the word of mouth effect. The word of mouth affects an organization or company´s reputation in other words called goodwill. We have focused this thesis in how a university works to create positive word of mouth and thereby indirect goodwill and to see how this work is perceived by students at the university. We did qualitative case studies and the data was collected though an interview and a focus group. The result shows that the work in this case Luleå University of Technology does in creating a positive word of mouth don´t match in all cases how student´s perceives it. We have from the result giving some suggestions for Luleå University of Technology in order to improve the word of mouth. Validerat; 20110610 (anonymous)